2020
DOI: 10.1038/s41598-020-73721-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antitumor effects of PP242 in a colon cancer xenograft mouse model using comprehensive metabolomics and lipidomics

Abstract: PP242, an inhibitor of mechanistic target of rapamycin (mTOR), displays potent anticancer effects against various cancer types. However, the underlying metabolic mechanism associated with the PP242 effects is not clearly understood. In this study, comprehensive metabolomics and lipidomics investigations were performed using ultra-high-performance chromatography-Orbitrap-mass spectrometry (UHPLC-Orbitrap-MS) in plasma and tumor tissue to reveal the metabolic mechanism of PP242 in an LS174T cell-induced colon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…PE is found predominantly within the mitochondrial membrane and is involved in cell proliferation and differentiation, as well as the possibility of cell apoptosis . The decrease in the PC/PE ratio will destroy the integrity of the hepatocyte and mitochondrial membrane, affect cell growth, and induce apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…PE is found predominantly within the mitochondrial membrane and is involved in cell proliferation and differentiation, as well as the possibility of cell apoptosis . The decrease in the PC/PE ratio will destroy the integrity of the hepatocyte and mitochondrial membrane, affect cell growth, and induce apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that the downregulation of PC and upregulation of lysoPC could induce cell apoptosis ( Anthony et al, 1999 ; Cui and Houweling, 2002 ; Takahashi et al, 2002 ). In the research of the antitumor effects of PP242, an inhibitor of mechanistic target of rapamycin (mTOR), in a colon cancer xenograft mouse model, Rashid et al (2020) indicated that lysoPC (18:2) in the PP242-treated mice was significantly increased after mTOR inhibition. It has also been suggested that lysoPC (16:0) induces apoptosis in human endothelial cells through a p38-MAPK-dependent pathway ( Takahashi et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…36–38 Furthermore, the down-regulation of phosphatidylethanolamine in disease groups caused disturbance to glycosylphosphatidylinositol (GPI)-anchor biosynthesis and glycerophospholipid metabolism, which could affect the integrity of the mitochondrial membrane, and cell proliferation, differentiation and apoptosis. 39–42…”
Section: Resultsmentioning
confidence: 99%